Influence of three-tire digital divide on self-rated health and life satisfac-tion among 18 - 54 years old digital natives and immigrants in China: an analysis on CFPS data of 2014, 2016 and 2018 - Yushan DU; Yafan WANG; Ziyang REN; Fengrui YANG; Yating LIU; Xinru LIU; Jufen LIU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo investigate the influence of the three-tier digital divide on self-rated health and life satisfaction among Chinese digital natives and digital immigrants, with the aim of bridging this divide and promoting public health. MethodsThe panel data on 12 967 residents aged 18 - 54 years at enrollment in 2014 and followed up in 2016 and 2018 were collected from three surveys of the China Family Panel Studies (CFPS). The analysis classified individuals aged 18 - 34 years as digital natives and those aged 35 - 54 years as digital immigrants. The participants' experiences of the digital access/use/literacy divide were evaluated based on their internet usage, weekly online engagement, and information literacy skills. A fixed-effect panel logit model was employed to examine the impact of the three-tier digital divide on the self-rated health and life satisfaction of both digital natives and immigrants. ResultsOf the 12 967 participants, 34.3% (4 448) were digital natives and 65.7% (8 519) were digital immigrants. Among the digital natives, 71.6% reported internet usage, with a median (25th, 75th percentile) of 10.0 (4.0, 20.0) hours per week for online engagement and a median information literacy score of 4.0 (3.0, 5.0); in contrast, among the digital immigrants, the reported proportion of internet usage was only 20.7%, with medians of 7.0 (3.0, 14.0) hours per week for online engagement and an information literacy score of 4.0 (3.0, 5.0). After controlling for gender, education level, marital status, place of residence, self-rated socio-economic status, and chronic disease condition, the results of fixed-effect panel logit analysis revealed that among digital natives, there was a negative correlation between life satisfaction and digital access discrepancy (odds ratio [OR] = 0.821, 95% confidence interval [95% CI]: 0.694 - 0.972); additionally, both self-rated health (OR = 1.179, 95%CI: 1.054 - 1.319) and life satisfaction (OR = 1.135, 95%CI: 1.051 - 1.225) were positively correlated with digital literacy discrepancy; whereas among digital immigrants, there was a positive correlation between life satisfaction and digital literacy discrepancy (OR = 1.121, 95%CI: 1.032 - 1.217). ConclusionThe three-tier digital divide impacts the self-rated health and life satisfaction of young and middle aged residents who are digitally native and those who are digital immigrants and the impact of digital literacy divide is more significant.